Risk Rating of Precast Concrete Pile Fabrication Process: A Case Study in Bandung, Indonesia - Firdaus, Adrian; Adianto, Yohanes Lim Dwi; Wijaya, Kevin Cornelius (Applied Science and Engineering Progress, 2019)
The utilization of precast concrete pile has become prevalent in Indonesian construction industry. The business process within the fabricator of precast concrete pile includes fabrication and installation process. This study is intended to fill research gap in fabrication process since most of the risk studies focus on the installation process. This study is aimed to identify and rate all risks related to the precast concrete pile fabrication process, followed by a recommendation of mitigation strategy. The preliminary risks are identified through field observation to a precast concrete pile fabricator in Bandung, Indonesia. The preliminary risks are validated using Delphi technique, resulting 22 final risk factors. The final risk factors are rated using risk matrix method. The high and medium category of the rated risks are sling failure; bar-cutter and/or bar-bender machine failure; hoist crane failure; and pile chip defect. Since most of those risks occur on the respective machine, the general mitigation strategies are to provide a backup machine and the frequent monitoring and maintenance. Besides, an adequate standard operation procedure of each fabrication stages needs to be established and its implementation should be monitored carefully.